Three Essays on Tax Avoidance, Audit Pricing and Asymmetric Cost Behaviour: Evidence from M&A Activities in the U.S. - Aldaham, Meshal (Curtin University, 2022)
This thesis comprises three essays that examine the relationship between mergers and acquisitions (M&As) and corporate tax avoidance, audit pricing and asymmetric cost behaviour in a large sample of U.S. firms.